Buccal Midazolam Compared With Rectal Diazepam Reduces Seizure Duration in Children in the Outpatient Setting. Issue 11 (November 2019) - Moretti, Raffaella; Julliand, Sebastien; Rinaldi, Victoria Elisa; Titomanlio, Luigi
Abstract : Background: Seizures are very common in children. They frequently happen in outpatient settings, in the presence of caregivers who are not always trained in their management. First-line rescue therapy is based on benzodiazepine, historically diazepam. Recent studies have investigated the use of other benzodiazepines in the treatment of acute seizures. Objectives: The aims of this study were to evaluate the management of pediatric seizures carried out by parents or caregivers in an outpatient setting and to evaluate the differences in terms of immediate management and subsequent outcome when comparing the use of rectal diazepam versus buccal midazolam. Methods: In this retrospective study, medical records of children consulting for seizures at the Robert Debré Pediatric Emergency Department of Paris, France, over 18 months were analyzed to evaluate seizure characteristics, management by caregivers, received treatments, and the admission rate. Results: Five hundred ninety-four patients resulted eligible for the study. The interview was completed for 135 children who presented a further episode of seizure after inclusion. In the subgroup of children receiving buccal midazolam, compared with the subgroup receiving intrarectal diazepam, seizure duration was significantly shorter (10.3 vs 48.4 minutes, P = 0.0004), and the risk of a status epilepticus decreased (1 vs 11, P = 0.0008). The admission rate was not different between the 2 subgroups. Conclusions: Based on our results, buccal midazolam seems to have some advantages compared with rectal diazepam in terms of feasibility in an outpatient setting and in terms of reduced seizure duration. Abstract : Supplemental digital content is available in the text.